Retinal Periphery Is Insensitive to Sudden Transient Motion. (June 2020) - Anstis, Stuart
Peripherally viewed targets moved around against a background of random dynamic noise. Slow movements were visible, fast movements were not. Thus, a target that repetitively drifted to the right and snapped back appeared to drift endlessly to the right with no visible snapbacks.